MARGANEC KIRISPE ATOMLARÍNÍŃ KLASTERLERINE IYE KREMNIYDIŃ TIYKARǴÍ PARAMETRLERINE BASÍMNÍŃ TÁSIRIN ÚYRENIW - Tursınbaev, S.A. (SCIENCE and SOCIETY, 2025)
This article experimentally investigates the effect of external pressure on the electrophysical properties of manganese-doped silicon. The diffusion of manganese atoms was carried out in p-type monocrystalline silicon samples. The results indicate that the presence of manganese clusters enhances the material’s high strain sensitivity. This material is considered promising for the development of high-sensitivity strain sensors.